STRATEGI BRANDING DAN PROMOSI PESANTREN DARUL LUGHAH WA DA’WAH MELALUI TIKTOK - Abidin, Zainal; Baharun, Segaf; Fauzi Hamzah, Achmad (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2024)
This research explores the branding and promotion strategies carried out by the Darul Lughah Wa Dakwah Bangil Islamic Boarding School through the TikTok platform, with the aim of understanding the effectiveness and resistance to the use of social media in the context of Islamic educational institutions. Using a qualitative approach and case study design, this research collected data through in-depth interviews, participant observation, and analysis of related documents. The 7C Framework approach—which includes Context, Content, Community, Customization, Communication, Connection, and Commerce—is used to analyze Islamic boarding school branding strategies. The findings show that TikTok plays an important role in expanding promotional reach and building a positive image of Islamic boarding schools through creative content showing daily life in Islamic boarding schools, testimonials, and educational content. However, significant challenges such as content conformity with Islamic values, balance between cyberspace and spiritual life, and data security and privacy need to be addressed to ensure the effectiveness and sustainability of branding strategies on digital platforms. This research provides insight into how Islamic educational institutions can utilize social media effectively while maintaining spiritual principles and data security. Keywords: Strategy, Branding, Promotion, TikTok